Management of blood lipid profile and oxidative status in Holstein and Simmental dairy cows during lactation - Obućinski, Dejan (Array, 2019)
Managing and determination of the blood lipid profile and oxidative status are useful tool to show the influence of foreign chemical substances on production of dairy cows. Investigation of various biomarkers of oxidative stress related to various problems in the production dairy cows presents a very important issue. The aim of this research was to investigate different biological markers in two different breeds of dairy cows – the Holstein Friesian and the Simmental, during different stages of lactation. The total of 60 Holstein Friesian and Simmental cows were divided into two treatments (HF and S) which was further divided into three groups each, respectively. Lactating groups of each cow breed was divided into three stages at early lactation of 32-75 days (HF1 and S1), peak lactation of 80-165 days (HF2 and S2) and low lactation of 175 days onward (HF3 and S3). During the research the total milk production and the percentage of milk fat and protein were determined. Blood samples were collected from jugular vein of each cow, the serum was harvested without anticoagulant and stored at -20 °C in small aliquots till further analysis. Serum was then analyzed for triglyceride, cholesterol, HDL, LDL, AST, ALT, GGT, the total antioxidant status (TAS), the total oxidant status (TOS), MDA, SOD, catalase and paraoxonase (PON1). Significantly (P<0.05) higher values of cholesterol, TOS and SOD at peak lactation stage was observed in all cows. A gradual decline from early lactation to low lactation was observed in the values of triglycerides and ALT, while MDA gradually increased from the same stage in all cows. The values of LDL and catalase showed an irregular pattern of variations in various lactation stages among all groups. The Holstein Friesian breed showed significantly higher values of ALT and PON1, while values of HDL, TAS and TOS were the lowest in Simmental group (P<0.05).